Critical Role of Interface and Crystallinity on the Performance and Photostability of Perovskite Solar Cell on Nickel Oxide. Issue 5 (11th December 2017) - Nie, Wanyi; Tsai, Hsinhan; Blancon, Jean‐Christophe; Liu, Fangze; Stoumpos, Costas C.; Traore, Boubacar; Kepenekian, Mikael; Durand, Olivier; Katan, Claudine; Tretiak, Sergei; Crochet, Jared; Ajayan, Pulickel M.; et al.
Abstract: Hybrid perovskites are on a trajectory toward realizing the most efficient single‐junction, solution‐processed photovoltaic devices. However, a critical issue is the limited understanding of the correlation between the degree of crystallinity and the emergent perovskite/hole (or electron) transport layer on device performance and photostability. Here, the controlled growth of hybrid perovskites on nickel oxide (NiO) is shown, resulting in the formation of thin films with enhanced crystallinity with characteristic peak width and splitting reminiscent of the tetragonal phase in single crystals. Photophysical and interface sensitive measurements reveal a reduced trap density at the perovskite/NiO interface in comparison with perovskites grown on poly(3, 4‐ethylene dioxy thiophene) polystyrene sulfonate. Photovoltaic cells exhibit a high open circuit voltage (1.12 V), indicating a near‐ideal energy band alignment. Moreover, photostability of photovoltaic devices up to 10‐Suns is observed, which is a direct result of the superior crystallinity of perovskite thin films on NiO. These results elucidate the critical role of the quality of the perovskite/hole transport layer interface in rendering high‐performance and photostable optoelectronic devices. Abstract : Highly crystalline perovskite thin film can be grown on nickel oxide substrates evidenced by sharp X‐ray diffraction pattern with characteristic tetragonal peak splitting observed only in single crystal. As a consequence, high‐efficiency photovoltaic cells can be achieved with extended operation lifetime under constant illumination benefit by the high degree of crystallinity.